2021
DOI: 10.1080/03081087.2021.1983513
|View full text |Cite
|
Sign up to set email alerts
|

The p-norm of circulant matrices

Abstract: The p-norm of circulant matrices JMM 2022Ludovick Bouthat (Université Laval)The p-norm of circulant matrices JMM 2022 4 / 26Permutation-invariant matrix normfor every permutation matrix P and Q. ExampleEvery matrix norm induced by a permutation-invariant vector norm is a permutation-invariant matrix norm.Ludovick Bouthat (Université Laval)The p-norm of circulant matrices JMM 2022 6 / 26

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…As observed in [1], A " Apn, a, bq, a P R, b ě 0 is self-adjoint and hence }A} p " }A} q , for p and q satisfying 1 p `1 q " 1 (see [6]). Thus, it suffices to focus on either p P p1, 2s or p P r2, 8q.…”
Section: Results and Proofsmentioning
confidence: 99%
See 2 more Smart Citations
“…As observed in [1], A " Apn, a, bq, a P R, b ě 0 is self-adjoint and hence }A} p " }A} q , for p and q satisfying 1 p `1 q " 1 (see [6]). Thus, it suffices to focus on either p P p1, 2s or p P r2, 8q.…”
Section: Results and Proofsmentioning
confidence: 99%
“…Circulant matrices arise in many applications ranging from wireless communications [2] to cryptography [3] to solving differential equations [4] (see [1] and the references therein for the historical context and more recent theoretical studies on circulant matrices). A circulant matrix is of the form , where a j P R, 1 ď j ď n. For a matrix A P R nˆn , we define the operator norm }A} p " sup x‰0 }Ax} p }x} p , for 1 ď p ď 8, where, for a vector y " py 1 , .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in [5] and [6], the following lower and upper bounds for the Chebyshev radius were obtained:…”
Section: Proof Without Loss Of Generality Sincementioning
confidence: 99%
“…We know from Corollary 6.6 that the Chebyshev radius of Ω n relative to the metric space (Ω n , • ℓ p n →ℓ p n ) is given by J n − I n ℓ p n →ℓ p n . Motivated by this result, the operator norm from ℓ p n to ℓ p n of the matrices of the form αI n + βJ n was studied and partial results were presented in [6]. In particular, it was showed that,…”
mentioning
confidence: 99%